A transformative university learning experience contributes to sustainability attitudes, skills and agency. (20th September 2019) - Probst, L.; Bardach, L.; Kamusingize, D.; Templer, N.; Ogwali, H.; Owamani, A.; Mulumba, L.; Onwonga, R.; Adugna, B.T.
Abstract: Given that graduates of higher education institutions will be the future decision makers addressing sustainability challenges, this study assesses the effects of a transdisciplinary university learning program on sustainability attitudes, skills, and agency. We investigated these variables with a sample of 117 previous participants in the International Training Course on Organic Agriculture, which took place in Uganda. To frame the analysis, concepts of sustainability learning and transformative learning were transferred into a research instrument, building on the Graduate Study Cooperative survey, the Transformative Learning Survey, and the Environmental Attitudes Inventory. The findings showed that the training course provided a transformative experience that positively predicted 1) environmental attitudes; 2) professional and personal competencies at graduation; 3) the feeling of being able to personally influence sustainability and the perception that one's employer has an influence on sustainability. No significant relation between the transformative experience and engagement in voluntary work was found. While ex post facto studies based on self-reported perceptions have limitations, this is—to our knowledge—the first study to apply the Transformative Learning Survey combined with other instruments to a specific learning intervention. By showing that transformative university learning experiences can contribute to sustainability attitudes, skills, and agency, the findings support the case for transdisciplinary course designs rooted in real-world sustainability challenges. Further research will be necessary to firmly establish the sustainability learning potential of different educational designs.